Penerapan Keselamatan Dan Kesehatan Kerja (K3) Di PT. X Pada Proyek RSPTN Universitas X - Vivi Selinda; Sulastri Sulastri; Panisean Nasoetion (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2026)
The implementation of Occupational Safety and Health (OSH) is a crucial aspect in construction projects to minimize workplace accidents and improve labor productivity. This internship report aims to evaluate the implementation of the OSH system at PT. X on the RSPTN Universitas X Project. The methods used include field observations, interviews with related personnel, and documentation review. The results indicate that OSH implementation has been carried out through the provision of personal protective equipment (PPE), safety induction programs, installation of safety signs, and routine supervision. However, several violations in PPE usage were still observed. Consistent and continuous OSH implementation is necessary to achieve the zero accident target in the project environment.